Consent to research participation: understanding and motivation among German pupils - Reetz, Jana; Richter, Gesine; Borzikowsky, Christoph; Glinicke, Christine; Darabaneanu, Stephanie; Buyx, Alena (BMC Medical Ethics, 2021)
Background: The EU’s 2006 Paediatric Regulation aims to support authorisation of medicine for children, thus effectively increasing paediatric research. It is ethically imperative to simultaneously establish procedures that protect children’s rights. Method: This study endeavours (a) to evaluate whether a template consent form designed by the Standing Working Group of the German-Research-Ethics-Committees (AKEK) adequately informs adolescents about research participation, and (b) to investigate associated phenomena like therapeutic misconception and motives for research participation. In March 2016 a questionnaire study was conducted among 279 pupils (mean age 13.1 years) of a secondary school in northern Germany. Results: A majority of participants showed a general good understanding of foundational research ethics concepts as understood from the AKEK consent form. Nevertheless, our data also suggests possible susceptibility to therapeutic misconception. Own health concerns and pro-social considerations were found to be significant motivational factors for participating in research, while anticipation of pain lessens likelihood of participation. Advice from trusted others is an important decisional influence, too. Furthermore, data security was found to be a relevant aspect of adolescents’ decision-making process. Conclusion: Bearing in mind adolescents’ generally good understanding, we infer the lack of knowledge about medical research in general to be one source of therapeutic misconception. To further improve the quality of consent we propose a multi-staged approach whereby general research education is completed before an individual becomes a patient or potential participant. To the best of our knowledge this is the first German questionnaire-study addressing issues of informed consent in a large under-age sample.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Data protection; Informed consent; Medical research; Paediatric consent; Therapeutic-misconception; Understanding